The Rural Tourist Entrepreneurship – New Opportunities of Capitalizing the Rural Tourist Potential in the Context of Durable Development - Razvan Catalin Dobrea, Marian Nastase, Ionica Soare, Nicoleta Cristache (European Journal of Sustainable Development, 2017)
The present paper aims to analyze the economic impact of developing an integrated pattern of entrepreneurship in rural tourism, on the basis of a complex process of monitoring the factors that have helped the rural communities to develop successfully, as well as through capitalizing the opportunities provided by the ensemble evolution of the national economic system. In the context of the theoretical researches regarding the standardization of terminology of rural tourism we have highlighted the effects of the economical social implications of rural tourism on the economical flows at national level. The increase of the offsets between the countries of the European Union regarding the tourist activity at rural level, is an issue of special interest which needs a process of constant analysis and intervention. The premises of European politics regarding rural development, through the support granted to foodstuff production, have allowed the concentration of the study on the identification and analysis of an entrepreneurship network with registered traditional agro-foodstuff products from rural area. The results obtained have highlighted the possible chances of revitalizing certain communities from mountainous and adjacent areas they have at their disposal, by capitalizing the potential provided ensured by the regional foodstuff patterns. The evaluation of the development potential of the mountainous tourism, based on the zone food system was performed based on the rural touristic entrepreneurship ratio – RTER. The paper also provides an overview on the setting up method of a ratio which highlights the potential of rural touristic entrepreneurship – RPRTE. Keywords: rural tourism, entrepreneurship, registered traditional products, underprivileged areas, and tourist potential